The Impact of Information and Word of Mouth on Customer Decisions to Use Mudharabah Savings at PT. Bank Syariah Indonesia Makassar Branch - Verawaty Verawaty (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2021)
The aim of the research is to evaluate and ascertain the impact of information and word-of-mouth on customer decisions to use mudharabah savings at the PT Bank Syariah Indonesia Makassar Branch. Instrument evaluation, Likert scale tests, multiple linear regression analysis tests, conventional assumption tests, heteroscedasticity tests, hypothesis tests, and determination coefficient (R2) tests are some of the data analysis methods used. The findings of this study demonstrate that customers' decisions to employ mudharabah savings at PT Bank Syariah Indonesia Makassar Branch are significantly and positively affected by the limited understanding test. Word-of-mouth influences customers' choices to use the PT Bank Syariah Indonesia Makassar Branch mudharabah savings in a favorable and negligible way. At the PT Syariah Indonesia Makassar Branch, consumers' decisions to use personal mudharabah funds are significantly influenced by their knowledge and word of mouth.